1998
DOI: 10.1520/jte11994j
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Strength of Resistance Spot Welds Subjected to Combined Tension and Shear

Abstract: A new test setup and data concerning the ultimate strength behavior of resistance spot welds in a mild strength steel subjected to combined tension and shear loads are presented. A test plan based on a design of experiments (DOE) with three design factors (coupon width, coupon length, and nugget diameter) was conducted to investigate the influence of the factors on the ultimate strength of the resistance spot welds under different loading angles. In this program, test loads were monotonically applied to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Different three-stack-up forms will fracture at distinct initiation angles. Lee et al 25 found that an increase in the rotation angle (α) between the sample interface and the tensile-shear direction reduces the peak load. Different restrictive effects on the weld rotation of the four joint designs were found in the present work.…”
Section: Results Of Tensile Shear Tests and Force Analysismentioning
confidence: 99%
“…Different three-stack-up forms will fracture at distinct initiation angles. Lee et al 25 found that an increase in the rotation angle (α) between the sample interface and the tensile-shear direction reduces the peak load. Different restrictive effects on the weld rotation of the four joint designs were found in the present work.…”
Section: Results Of Tensile Shear Tests and Force Analysismentioning
confidence: 99%